The axial and radial phase holdup distribution of bubble-induced three-phase inverse fluidized bed. (29th June 2020) - Ma, Keying; Liu, Mingyan; Chen, Shaoqi; Shao, Yuanyuan; Zhu, Jesse
Graphical abstract: Highlights: The axial and radial phase holdup distributions of BIFB were investigated in detail. A new vision probe was applied first in multiphase fluidization system. A new data processing method was proposed to obtain the solid holdup. Axial distributions of the solids holdup are less uniform at low/high gas veloctity. Radial distributions of solids holdup are nearly constant except the wall region. Abstract: The detailed phase holdup distributions in a 0.33 m ID & 3 m height cylindrical bubble-induced three-phase inverse fluidized bed (BIFB) with air, water and polyethylene particles were investigated using a relatively new telecentric photographic probe. In the complete fluidization regime, the axial and radial distributions of the phase holdups were studied in detail. The axial gas holdup distribution is largely uniform at a low gas velocity and increasing the gas velocity leads to more nonuniformity with a higher gas holdup at the top due to the difference of the bubble size. The solids holdup distribution is less uniform but more uniform axial distribution was observed with the gas velocity as the upper particles being gradually entrained downwards. The liquid holdup is always high in the top region. The effect of the gas velocity and the axial height on the radial distributions of the phase holdups also were discussed.